The trend and evolution of training in volleyball: A bibliometric analysis of the last five years - Saharullah; Siregar, Faris Zhafran; Nur, Abidah; Hermawan, Iwan; Medeiros, Alexandre Igor Araripe (UIR Press, 2024)
Background Problems: The main focus on improving the performance of volleyball players and teams is through training that covers various aspects. Research Objectives: This study aims to analyse and explain trends and developments in the scientific literature regarding volleyball training over the past five years while identifying the most frequently featured training concepts, methods, and techniques in bibliometric studies in the field over the same period. Methods: Publication records between 2019 and 2023 were extracted from Scopus and the Web of Science, after which the bibliographic data set was administered using ScientoPy and VOSviewer. A term search was conducted with the keywords “training” OR “exercise” OR “practice” AND “volleyball”. Findings and Results: Results showed a total of 1.105 papers were published over the past five years, with 2022 recording the highest number of articles. The International Journal of Environmental Research and Public Health was the most prolific source, with 45 papers, and Clemente, F. M., was the most published author. The United States was the leading contributor in this research domain with 137 papers. The most frequently highlighted training concepts, methods, and techniques in this topic included vertical jumps, biomechanics, body composition, muscle strength, power, endurance training, injury prevention, agility, balance, and countermovement jumps. Conclusion: The results of this study emphasise the importance of developing training-related knowledge in volleyball. For future research contributions and recommendations, some things that can be taken into consideration are increased interdisciplinary studies, more applied research, use of technology in training, focus on health and injury prevention, comparative studies between countries, and research related to youth training in volleyball. This research provided a strong foundation for further development in understanding and optimising the training of volleyball players in the future.